Drawing-to-Learn: Active and Culturally Relevant Pedagogy for Biology - Edlund, Anna F.; Balgopal, Meena M. (Frontiers in Communication, 2021)
Students enter biology classrooms with ideas about the natural world already formed. Teachers can help students construct new knowledge by using active, culturally relevant pedagogy and by making space in their lesson for students to reveal, challenge, and/or reconcile their preconceptions with new knowledge. Drawing meets all of these needs. Drawing-to-learn (DTL) allows students to be metacognitive and creative as they generate concrete representations of their abstract conceptions. In this case study of biology classes for Tibetan Buddhist monastic students through the Emory-Tibet Science Initiative, we find that DTL engages students in active learning, allows multi-modal visualization and discourse about mental models, and beyond this, solicits cultural references from both students and teachers.